Determinants of Halal Tourism Intention in Jabodetabek Indonesia - Pulungan, Nur Azizah; Indra (SMART Insight, 2023)
The purpose of this study is to analyze how the influence of psychographic, socio-demographic, and geographical segmentation on public interest in halal tourism and to analyze the role of the government in the development of halal tourism. This study uses the method of Structural Equation Model (SEM) analysis and qualitative descriptive analysis methods. The data from this study were obtained from primary data (questionnaires) and secondary data (books, journals). The questionnaires were distributed online in the Jabodetabek area. The results obtained in this paper are from 3 variables of tourist characteristics in halal tourism, there is 1 variable that is considered to not affect the wishes of tourists in halal tourism. From psychographic, socio-demographic, and geographic variables, the variable that does not affect the desire of tourists to travel halal is psychographic. Meanwhile, several government's strategies in developing halal tourism are: Making regulations that can simplify and lighten the management of halal certification; Marketing 10 halal tourism destinations to foreign tourists; Conducting guidance for community economic empowerment that supports the operation of the halal tourism sector in Indonesia; and Good management of the halal tourism sector and good corporate governance.